Modeling and constrained optimal design of an ultra-low-friction pneumatic cylinder with air bearing - Jian Cao; Xiaocong Zhu; Feiteng Li; Xin Jin (Advances in Mechanical Engineering, 2019)
The ultra-low-friction pneumatic cylinder has promoting applications in high-precision motion control and load simulator systems owing to its capability of attenuating stick-slip behavior at low speed and easily realizing accurate force at high speed. A pneumatic cylinder with an aerostatic bearing as its piston is recently proposed to achieve ultra-low friction. Two mathematical models that, respectively, consider one-dimensional flow and two-dimensional flow through the air film between the cylinder piston and the cylinder wall are developed to predict performance characteristics of the system working at different load conditions. The multiple design parameters are lumped into non-dimensional structural parameters and environmental parameters. Then, a constrained optimal design method is developed to achieve prior performance with smallest leakage flow rate for better dynamic response and appropriate radial load carrying capacity for supporting the floating piston itself. Performance comparison addresses the important influence of lumped non-dimensional parameters and unified assessments of two models for the ultra-low-friction pneumatic cylinder. The available optimal design parameters and achievable performances are indicated.